Pengembangan LKPD Berorientasi STEM dengan Model PjBL Materi Larutan Elektrolit Nonelektrolit dengan Memanfaatkan Bahan Sekitar - Anisatul Ma'sumah; Mitarlis Mitarlis (Jurnal Inovasi Pembelajaran Kimia (Journal Of Innovation in Chemistry Education), 2021)
The aim of this research is producing student worksheets STEM-oriented with PjBL model of electrolyte and non-electrolyte matter by utilizing surrounding materials. This study used 4-D development model (four-D model), which is a development model consisting of 4 main stages: Define, Design, Develop, and Disseminate. This research was limited to the develop stage and limited trials were carried out on 9 students of SMAN 1 Gedangan Sidoarjo. The feasibility of student worksheets is seen based on aspects of validity, practicality, and effectiveness. This research shows the results of the validity student worksheets on the content criteria as 85.84% and the construct validity of 86.56% on very good category. The results of students' responses to the student worksheets obtained a percentage of 96.67% on very practical category, observation of the first to the third meetings obtained an average percentage of 90.65% on very practical category. The results effectiveness of the student worksheets obtained an average N-Gain score of 0.83 with a high category which proved that the learning outcomes of students have increased on the tests before and after learning to use student worksheets.